Investigation of ethanol, acetone and aqueous azadirachta indica A. Juss (NEEM) extracts against plasmodium falciparum - Ghazali, Siti Zulaiha (2022)
Malaria is a public health concern, causing significant morbidity and mortality annually due to the emergence of drug-resistance parasites. Therefore, the need for novel antimalarial agents with novel mechanisms of action and broad therapeutic potential is critical. In this study, Azadirachta indica A. Juss (Neem), a long-used herbal remedy has been chosen due to the scarcity of data on Malaysian Neem on its antimalarial property. Thus, this study aimed to determine in vitro antimalarial activity of Malaysian’s Neem leaves crude extracts against laboratory-adapted, sensitive (3D7) and chloroquine-resistance (W2) P. falciparum strains. At first, all the collected leaves were taxonomized by The Forest Research Institute Malaysia (FRIM) and further authenticated molecularly before extraction with ethanol, acetone and aqueous followed by a phytochemical screening of the extracts. DPPH radical scavenging is used to determine antioxidant activity before GC-MS profiling. The brine shrimp lethality test (BSLT) and a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay against the primary human umbilical vein endothelial cells (HUVEC) were used for toxicity assay. The antimalarial activity was determined using the malarial SYBR Green I fluorescence-based assay against both strains. The study was extended with a green synthesis of Neem-silver nanoparticles (AgNPs) and further evaluated on their antimalarial property. Our data showed that crude extract produced by acetone (15.55 ± 0.04%) and ethanol (9.20 ± 0.05%) using the soxhlet method produces more yield compared to aqueous extract (5.86 ± 0.06%). However, aqueous extract contained the highest total phenolic and flavonoid content. Meanwhile, the brine shrimp lethality test and MTT assay showed all extracts are not toxic with LC50 > 1000 ppm and CC50 values > 30 g/mL, respectively. Whereas, all extracts showed a moderate antimalarial effect against 3D7. However, acetone and aqueous extract showed inactive antimalarial activity against W2 (IC50 > 50 ug/mL). On the other hands, when Neem combined with nano silver (Neem-AgNO3), it showed a 4-folds increment of antimalaria activity against 3D7 (IC50 = 8.815 ± 0.230) and W2 (IC50 = 23.110 ± 0.088). Thus, this study showed promising antimalarial activity of Malaysian Neem when combining with nanoparticle and should be further evaluated of its property to overcome the chloroquine resistance in malaria treatment.